Automatic Task Planning and Its On-Orbit Verification of Agile Remote Sensing Satellite - Zhang Yahang; Yang Haiyue; Yang Mengfei; Yang Ruochu; Leng Shuhang (International Journal of Aerospace Engineering)
An on-board autonomous task planning system is designed and implemented in this article, aiming at the problem that the current remote sensing satellite needs complex instruction support to perform tasks and depends on the ground system too much. The complex earth observation task description and injection decomposition modules are designed in the system. No more than 128 ordered points describe the curve area task or irregular polygon area task, and the complex task is decomposed into several strips according to the satellite imaging width. Then, the task’s orbit, attitude, mobility, energy, and time constraints are calculated through the modules of on-board orbit prediction, agile attitude calculation, track planning, energy prediction, and visible arc calculation. Finally, the on-board autonomous task planning and execution are completed through task solution space search and metatask command generation modules. The on-orbit flight verification is carried out on the high-resolution multimode (GFDM) satellite. The results show that this paper’s on-board autonomous task planning system can complete complex task injection and autonomous planning and finally execute.